Research methodology in strategy and management. Vol. 5 - Ketchen, David J.; Bergh, Donald D. (Research methodology in strategy and management., 2009)
This book series' mission is to provide a forum for critique, commentary, and discussion about key methodology issues in the strategic management field. Strategic management relies on an array of complex methods drawn from various allied disciplines to examine how managers attempt to lead their firms toward success. The field is undergoing a rapid transformation in methodological rigor, and researchers face many new challenges about how to conduct their research and in understanding the implications that are associated with their research choices. This book series seeks to bridge the gap between what researchers know and what they need to know about methodology. In each volume, renowned scholars contribute chapters in their areas of methodological expertise.